PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2008-2011 - Danny Oktanto; Muhamad Nuryatno Amin (Jurnal Akuntansi Trisakti, 2014)
The objective of this research is to examine the effect of financial ratios(proxied by liquidity ratios, solvency ratios, and the ratio of activity) to changes in earnings. Sample used is 55 manufacturing companies in listed in the Indonesian Stock Exchange’s between 2008-2011. Data used were secondary data from annual financial reports. The sampling technique used is purposive sampling method and the model analysis is multiple linier regression. The result indicated that not all independent variables showed significant influence on the dependent variable. Based on this research, solvency ratios and ratio of activity partially influenced to the changes in earnings, where as liquidity ratios doesn’t influence the change in earnings. Liquidity Ratios, Solvency Ratios, and Activity Ratios are used together have a significant impact on the change in earnings.